2016
DOI: 10.1007/s10113-016-1080-6
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in linking adaptation and mitigation in the forests of the Congo Basin

Abstract: Recent discussions on forests and climate change have highlighted the potential for conservation of tropical forests to contribute synergistically to both mitigation (reducing emissions of greenhouse gases) and adaptation (increasing capacity to cope with changing climate conditions). Key mechanisms through which adaptive advantages might be gained include the potential for forest resources to support livelihoods in the context of climatic strains on agriculture and the protection that intact forest ecosystems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
1
28
2
Order By: Relevance
“…This group will experience an increase in precipitation and a slight increase in PET/P that will result in higher R in tropical humid/subhumid basins. The same mechanism is also likely to promote nutrient loss because of the washout of the topsoil layer during extreme events, with negative consequences for agricultural productivity as already observed in the Congo basin (Few et al, 2014). However, the additional precipitation could likely come from stronger tropical cyclones (Knutson et al, 2010), thus increasing the R to P ratio and explaining the expected decrease in Sm.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This group will experience an increase in precipitation and a slight increase in PET/P that will result in higher R in tropical humid/subhumid basins. The same mechanism is also likely to promote nutrient loss because of the washout of the topsoil layer during extreme events, with negative consequences for agricultural productivity as already observed in the Congo basin (Few et al, 2014). However, the additional precipitation could likely come from stronger tropical cyclones (Knutson et al, 2010), thus increasing the R to P ratio and explaining the expected decrease in Sm.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, steady moderate P infiltrates more easily into the soil, increasing Sm, while the same amount of P concentrated in shorter periods causes higher R (possibly flooding) leaving soils eventually much drier (Trenberth et al, 2003). The same mechanism is also likely to promote nutrient loss because of the washout of the topsoil layer during extreme events, with negative consequences for agricultural productivity as already observed in the Congo basin (Few et al, 2014). National authorities should consider strengthening flood risk prevention plans, particularly in view of the expanding urban settlements.…”
Section: Discussionmentioning
confidence: 76%
“…As argued in other studies [18,21], projects aimed at modernizing and intensifying beekeeping and other activities traditionally linked to forest environments risk ignoring the ecological, technological, and socio-economic dynamics at play. The unfolding of these dynamics over time and space de nes the trajectories that the social-ecological systems will follow in terms of forest conservation, household and community resilience, and cultural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the adoption of modern hives has been slow as a result of their high cost for rural dwellers, the lack of training on how to manage them, and their scarce adaptability to forest ecologies [16,17]. Although some scholars have addressed drivers and variables connected to the adoption of modern beekeeping systems [13,14], there is still little information about the actual impacts of this innovation on traditional beekeeping-related ethnobotanical knowledge and practices and on the ways of living in the environment by local communities [18,19]. Other studies conducted in Africa [6,20] and elsewhere [21,22] have highlighted the di culties for intervention programs to strike a balance between fostering economic empowerment while promoting environmental conservation and supporting cultural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wüstemann et al (2017) examined how forest management practices in Germany can contribute to mitigation outcomes from ecosystem-based perspectives (Wüstemann et al, 2017). Other studies focused on how to protect forest resources so as to improve carbon sinks as well as ecosystem services (Locatelli et al, 2014), including livelihoods (Few et al, 2017), landscape conservation (Ingalls & Dwyer, 2016), ecological improvement and agricultural benefits (Salvini et al, 2016), and biodiversity Figure 2. Overview of the review analysis based on sector.…”
Section: Approaches For Mitigationmentioning
confidence: 99%